PELATIHAN PENGENDALIAN PENYAKIT TUNGRO DAN BLAS PADA TANAMAN PADI DI SUBAK BASANGKASA - TEMAJA, IGRM; SUDANA, M; SUDIARTA, IP; WIRYA, GNA SUSANTA; PUSPAWATI, NM (Buletin Udayana Mengabdi; Vol 14 No 1 (2015): April 2015, 2015)
Training on tungro and blast diseases was held at Subak Basangkasa, Kerobokan village, Badung regency on April 27, 2014. The activities was conducted to educate farmers how to control tungro and blast diseases. The methods used in this activity were lectures, demonstration and practice in the paddy field. The training was attended by 30 participants from local farmer groups of Subak Basangkasa. Based on post test, more than 90% of the farmers managed to answer the questions about tungro and blast diseases, including pathogens, symptoms of diseases, factors affecting the growing of diseases as well as the control of diseases. The data indicated on the final of training all participants completely understand about the topics. All participants participated enthusiastically and hope they have the next intensive training again. Key words :disease control, tungro disease, blast disease, trainin